A Note on Gluing Dirac Type Operators on a Mirror Quantum Two-Sphere - Klimek, S.; McBride, M. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
The goal of this paper is to introduce a class of operators, which we call quantum Dirac type operators on a noncommutative sphere, by a gluing construction from copies of noncommutative disks, subject to an appropriate local boundary condition. We show that the resulting operators have compact resolvents, and so they are elliptic operators.